A Study on Pressure Coefficient in Co-Current Three Phase Fluidization by Linear Regression Analysis - Sivalingam, A.; Kannadasan, T. (Asian Journal of Chemistry, 2011)
In this present work, a methodical study of the effect of fundamental and operating variables on pressure drop in a three-phase fluidized bed has been studied to detect the pressure coefficient. Pressure influences the hydrodynamics, heat and mass transfer properties of a three-phase fluidized bed considerably. Co-current three-phase fluidization using glass beads and gypsum as solid phase, water as liquid phase and air as gas phase was studied. By using dimensional analysis, pressure coefficient was determined for the fluidized bed with and without internals. The correlations constant are determined by linear regression using MATLAB program. The experimental values were compared and the equation is found to be valid. The correlation coefficient is estimated to be R2 > 0.9.